Catheter‐related thrombosis diagnosed by computed tomography. Issue 3 (3rd February 2017) - Yamauchi, Yohei; Baba, Akira; Okuyama, Yumi
Key Clinical Message: Catheter‐related bloodstream infection can be detected with CT. Although it is not mandatory for its diagnosis, it is strong evidence as a cause of fever if detected incidentally. Abstract : Catheter‐related bloodstream infection can be detected with CT. Although it is not mandatory for its diagnosis, it is strong evidence as a cause of fever if detected incidentally.